How well does political connection affect firms’ performance? / Nurul Azlin Azmi ...[et al.] - Azmi, Nurul Azlin; Zakaria, Nor Balkish; Abd Sata, Fazrul Hanim; Mohd Sanusi, Zuraidah; Busirin, Mohd Fazrin (UiTM Cawangan Johor, 2019)
The purpose of this study is to examine the influence of political connections on firms’ performance by controlling the effect of board attributes and firms characteristics. Specifically, it is argued that politically connected firms enjoy a lot of benefit from the government and said to provide greater chances for the firms to increase their wealth. By using 156 public listed firms between the study period of 2012 to 2017, this study maps out political connection based on the 13th Malaysian general election. The results reveal that the appearance of political connections on board give significant and negative effect on Tobin Q, while significant and positive effect on Return on Asset (ROA) and Return on Equity (ROE). Board independence is also significant to firms’ performance. This result implies that political connections are favour for a better firm’s performance and not to firm’s value. The findings have an important implication to investors as it suggest that firms with political connection on board perform better.